Effects of Cooperative Integrated Reading and Composition Learning Model on the English Learning Skills - Hadiwinarto Hadiwinarto; Novianti Novianti (Intelektual Pustaka Media Utama, 2015)
This research was aimed at describing the effects of Cooperative Integrated Reading and Composition (CIRC) learning model on the reading and writing skills of junior high school students in learning English. This research applied one group pretest-posttest design. Data were collected by using tests and analized by using descriptive analysis and t-test. The result showed that: the average score for reading skill before the experiment was 50.00 and the average score for reading skill after the experiment was 65.58. On the other hand, the average score for writing skill before the experiment was 38.21 and the average score for writing skill after experiment was 58.05. The implementation of CIRC learning model had very significant effects on the English reading and writing skills of the junior high school students.